Perspectives on the Arabic Language from University Student: Between Reality and Hope - Rijal Mahdi; Ahmad Asri Lubis (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
Learning Arabic language has the ideal conditions that students want to achieve. therefore, the ideal condition is highly dependent on various factors. This research discusses the views or perspectives on the Arabic Language from students of IAIN Syekh Nurjati Cirebon that are enrolled in different faculties. This research contains several objectives: primarily to learn the direct thoughts of students on the Arabic language and its relevance within both national and international level. In addition, this study reveals the academic conditions of the students that has a direct correlation towards their preparedness and desire to receive studying materials in one semester whilst studying during first semester 2019 in from the total amount of sample that consists of 109 students. The researcher utilizes the survey method to perform the study along with empty cards as an aiding tool which was distributed among students. The empty papers that were provided were given to let students write their brief reasonings behind their perspective on Arabic Language. The outcome of this study shows that there were 40% of students having negative views towards the Arabic language, 45% of students with positive views while 10% of the research sample combines themes or contents closely related to the Arabic language. Furthermore, 5% of student gave suggestions and ideas for learning Arabic language. This research has contributed in several ways especially in understanding the student’s perspectives and opinions on Arabic language and help the lecturers to identify suitable teaching methods to use during the learning and teaching process.